Balancing Variety and Quality: Examining the Impact of Benefit-Linked Cross-Subsidization on Multisided Platforms - Tavalaei, Mahdi; Gawer, Annabelle; Santaló, Juan (John Wiley and Sons Inc, 2024)
Multisided platforms face a fundamental trade-off: should they ease entry for a larger number of providers of complementary products or services (complementors) to join the platform and benefit from cross-side network externalities,or should they limit entry to maintain complementors’ incentives to provide high-quality offerings? We contend that a specific cross-subsidizing pricing strategy – where the amount of subsidy to complementors is explicitly linked to the overall revenue they generate on the other side of the platform – may mitigate this trade-off. Using data from the airport industry,we demonstrate that following a reduction of airlines’ entry barriers,airports that subsidize airlines,based on the aforementioned scheme,can boost their financial performance and maintain traffic composition in favour of legacy airlines,which bring passengers who spend more in airport shops. Our findings shed light on how cross-subsidization may balance the variety and quality of complementors and their offerings on multisided platforms. © 2024 The Author(s). Journal of Management Studies published by Society for the Advancement of Management Studies and John Wiley & Sons Ltd.
Keywords: Cross-subsidization pricing; Gatekeeping strategies; Multisided platforms; Network externalities; Variety vs. quality trade-off; 53 Ciencias Económicas; ODS 9 - Industria, innovación e infraestructura